Child Protection and Maqāṣid al-Sharī‘ah in Indonesian Marriage Dispensation Decisions - Firmansyah Pratama Alim; Gizca Mokodongan; Wira Purwadi; Ahmad Fakhrurrazi Mohammed Zabidi (Al-Mujtahid: Journal of Islamic Family Law, 2026)
Child marriage remains a persistent challenge in Indonesia despite the statutory increase of the minimum marriage age to 19. The marriage dispensation mechanism, while designed as a limited legal exception, often becomes a pathway through which underage marriage is judicially authorized. This study examines how judges construct considerations of child protection and maqāṣid al-sharī‘ah in Indonesian marriage dispensation decisions by comparing Decision No. 51/Pdt.P/2021/PN.Arm of the Airmadidi District Court and Decision No. 81/Pdt.P/2021/PA.Bit of the Bitung Religious Court. Using an empirical juridical method with a qualitative comparative approach, the study analyzes court decisions, relevant legislation, and interview data from judicial actors. The findings show that both courts granted dispensation but relied on different legal rationalities. The Airmadidi District Court emphasized factual urgency, cohabitation, reproductive health risks, educational disruption, economic readiness, and the best interests of the child. The Bitung Religious Court, while also applying statutory rules, framed urgency through Islamic legal reasoning, particularly the prevention of zina and the protection of lineage (ḥifẓ al-nasl). This study argues that marriage dispensation should not be treated merely as an emergency measure but as a child-protection test that requires a careful balance among maqāṣid al-sharī‘ah, legal certainty, and children’s long-term welfare.